2003
DOI: 10.1021/jp0305279
|View full text |Cite
|
Sign up to set email alerts
|

Cavity Ringdown Spectroscopy of the à − X̃ Electronic Transition of the CH3C(O)O2Radical

Abstract: Cavity ringdown spectra of the near IR A 2 A − X 2 A electronic transition of acetyl peroxy radical and its perdeutero analogue are reported. The electronic origin for the CH3C(O)O2 is observed at 5582.5(5) cm −1 . Extensive ab initio calculations have been carried out to predict frequencies and help assign the electronic origin, observed vibrational hot bands and severalà state vibrational frequencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
55
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(65 citation statements)
references
References 39 publications
10
55
0
Order By: Relevance
“…Note too that the IR spectra of C 2 H 5 OO and C 3 H 7 OO are both broad and weak. [15][16][17][18][19]…”
Section: -4mentioning
confidence: 99%
See 1 more Smart Citation
“…Note too that the IR spectra of C 2 H 5 OO and C 3 H 7 OO are both broad and weak. [15][16][17][18][19]…”
Section: -4mentioning
confidence: 99%
“…The à 2 AЈ ← X 2 AЉ transition of ROO in the near IR does display resolved vibrational and rotational spectra as reported by Hunziker et al using a modulation absorption technique 14 and by Miller et al using cavity ring down spectroscopy. [15][16][17][18][19] Characterization of the à 2 AЉ ← X 2 AЉ transitions of peroxy radicals not only yields information on their properties and reactivities, but also provides a sensitive and selective technique for their detection. This near IR transition has a small transition cross section ͑ ϳ 10 −21 -10 −22 cm 2 ͒; however, our recent results for supersonic beam samples combined with IR + VUV ͑118 nm͒ photofragmentation detected ͑PFD-IR͒ spectroscopy of the alkyl peroxy radical have proven that the IR+ VUV PFD-IR approach is sensitive enough to detect the à 2 AЈ ← X 2 AЉ transitions of alkyl peroxy radicals.…”
Section: Introductionmentioning
confidence: 99%
“…5,6,8 Briefly the second harmonic light from an Nd:YAG laser pumped a dye laser (20 Hz QuantaRay PRO-270 Nd:YAG, Spectra Physics SIRAH dye laser). The dyes used were DCM, Rhodamine B, and Rhodamine 101.…”
Section: Nir Crds Apparatusmentioning
confidence: 99%
“…1,2 The peroxyacetyl radical ͓PA, CH 3 C͑O͒OO͔ is one of the most important atmospheric peroxy radicals, and it can react with NO 2 to form peroxyacetyl nitrate ͓PAN, CH 3 C͑O͒OONO 2 ͔, an additional important atmospheric species that can serve as a temporary reservoir and transport molecule for NO x . 7 Recently, cavity ringdown absorption studies have been reported for peroxy radicals in this region, and sharp, structured, well-resolved spectra ͑at 300 K͒ have been detected for PA. 8 In this work flash pyrolysis, supersonic expansion, and infrared/ultraviolet ion enhancement spectroscopy techniques are employed to detect and study the PA radical à 2 AЈ ← X 2 AЉ transition. The low lying electronic transition to the à state, à 2 AЈ ← X 2 AЉ ͑ca.…”
Section: Introductionmentioning
confidence: 99%